2023
DOI: 10.15244/pjoes/156688
|View full text |Cite
|
Sign up to set email alerts
|

Research on Carbon Emission Efficiency and Its Improvement Path of China’s Provinces Based on SBM-ML Model and fsQCA Model

Abstract: The realization of the "double-carbon" goal will contribute to the high-quality and sustainable development of China's economy and society, while the improvement of carbon emission efficiency in Chinese provinces will lay a solid foundation for the realization of the "double-carbon" goal. In this paper, 30 Chinese provinces are selected as research cases. MatLab software is applied to build the slacks-based measure Malmquist-Luenberger (SBM-ML) model to measure carbon efficiency. By the analysis of their carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Liu Chao [38] and others employed the LSTM model to forecast carbon emissions and successfully realized the task of predicting carbon emissions and achieved remarkable results, which provided strong support for research and application in this field. Chun-Sen Liu and Jian-Sheng Qu [39] used LSTM for carbon emission forecasting in the transport industry, and the outcomes demonstrated that LSTM outperforms the BP neural network and SVR Machine, which demonstrates the exceptional performance of LSTM in the domain of carbon emission forecasting.…”
Section: Prediction Methods Based On Recurrent Neural Networkmentioning
confidence: 99%
“…Liu Chao [38] and others employed the LSTM model to forecast carbon emissions and successfully realized the task of predicting carbon emissions and achieved remarkable results, which provided strong support for research and application in this field. Chun-Sen Liu and Jian-Sheng Qu [39] used LSTM for carbon emission forecasting in the transport industry, and the outcomes demonstrated that LSTM outperforms the BP neural network and SVR Machine, which demonstrates the exceptional performance of LSTM in the domain of carbon emission forecasting.…”
Section: Prediction Methods Based On Recurrent Neural Networkmentioning
confidence: 99%